Sister City Cooperation Model In Wetland Environmental Governance: Case Study In Banjarmasin, South of Kalimantan - Mahyuni Mahyuni; Muhammad Najeri Syahrin (International Journal of Politic, Public Policy and Environmental Issues, 2021)
This study analyses the framework model cooperation of the sister city that the Banjarmasin city government will carry out in wetland environmental governance (wetland governance). The model of sister city cooperation design that will be carried out is through the bottom-up model cooperation. This cooperation model focuses on the active participation of the community (citizen diplomacy) and community collaboration as transnational actors in managing the wetland environment (wetland governance) in Banjarmasin. Community participation (citizen diplomacy) and the active collaboration of the community with the city government as a transnational actor has become a fascinating new study in government and international relations, so it is crucial to study further. The wetland environmental management model in this model is integrated wetland environmental management. So far, the integrated wetland environmental management planning methodology has paid little attention to aspects that integrate institutions, technology, and funding. This model also describes ideally that wetland environmental management accommodates various interests of development activities, such as agricultural development, industrial interests, and environmental carrying capacity (ecological demands). The operationalisation of the integrated wetland environment concept as a planning unit in development has been limited to rehabilitating and conserving soil and water. At the same time, the organisation is still ad hoc, and the intact institutions regarding the management of the wetland environment have not been patterned. For wetland environmental management to be carried out optimally, it must involve all stakeholders and plan in an integrated, comprehensive, sustainable, and environmentally friendly manner with wetlands as a management unit. The bottom-up sister, the city cooperation model, was then made based on these problems. This collaboration is an effort to involve all parties, especially the community, so that every decision taken in planning is a collective decision and encourages mutual involvement and commitment to implement it.